INFLAMATION AS A DEPRESSION-CAUSING FACTOR IN CHRONIC KIDNEY DISEASE PATIENTS - Eric Herlambang Sutantio (Journal of Psychiatry Psychology and Behavioral Research, 2020)
Chronic Kidney Disease (CKD) is a health problem and has an effect on nearly 10% of the global population. Patients with end-stage renal failure will face complications in all organ systems and the most common psychiatric complications are depression, anxiety, dementia, delirium, coping difficulties and marital or family problems. Even the prevalence of depression is higher in patients with end-stage kidney disease than the general population. Depression in CKD patients has been shown to be associated with poor outcomes in CKD patients. The complex interactions between CKD and depression are dynamic and multifactorial, including socio-economic, lifestyle and biological factors. Biological factors that are closely related to the incidence of depression in CKD include the immune system, inflammatory pathway disorders of the Hipothalamus-Pituitary Axis (HPA) and changes in the sympathetic and parasympathetic nervous system. Inflammatory factors as a cause of depression have been identified with high concentrations of pro-inflammatory cytokines found in patients who are clinically depressed as well as patients with depressive symptoms, especially IL-1Î², IL-6 and TNF-Î±. Furthermore, there is evidence to suggest that these pro-inflammatory cytokines interact with many pathophysiological mechanisms of depression, including neurotransmitter metabolism, neuroendocrine function, synaptic flexibility and behavior. Keywords: Inflammation, Chronic Kidney Disease, depression